Insecticide activity of native strains of Beauveria spp. and Metarhizium spp., against second instar larvae of Spodoptera frugiperda (Lepidoptera: Noctuidae) - APONTE, LIGIA; URIBE, DANIEL (Revista Colombiana de Entomología, 2001)
Spodoptera frugiperda (J.E. Smith) is a insect that is considered a pest in a great variety of crops in our country like cotton, rice, corn, and sorghum. In the American continent, it is widely distributed, that it is why some studies have been carried out developing some biological control strategies based on the natural enemies of the pest. In the present work, it is evaluated the biopesticide activity of native isolates of Beauveria spp. and Metarhizium spp. against second instar larvae of S. frugiperda, in order to bring out the knowledge of the biopesticide potential of some entomogenous fungí native strains. Great variability in terms of the biopesticide activity was observed when it was evaluated 30 isolates from different host insect and geographic places. Of the 30 ísolates. only 18 developed mycosis when they were passing through second instar larvae of the target insect. Those strains were tested in a bioassay by using 1x108 conidia.ml-1 against second instar larvae of S. frugiperda. In this phase. the variation in terms of mortality for the different isolates was between O and 93%. Seven of those isolates presented more than 50% of mortality, with an LT50 value between 1.41 and 6.31 days. In the second phase, the LC50 was evaluated to the entomogenous fungí isolates with the lower LT50. The LC50 values were between 8.2x106 and 1x108 conidia.ml-1. The Beauueria spp. isolates IBUN-B-59, IBUN-676 e IBUN-B-146 presented the highest percentage of mortality, the lower values of LT50 and LC50, and were very stable in terms of its biopesticide activity during the different evaluation phases, that is why it is suggested some field studies with those isolates.